Radiographic Variables That May Predict Clinical Outcomes in Cervical Disk Replacement Surgery. Issue 3 (April 2015) - Rihn, Jeffrey A.; Radcliff, Kristen; Hipp, John; Vaccaro, Alexander R.; Hilibrand, Alan S.; Anderson, David G.; Albert, Todd J.
Abstract : Study Design: Retrospective analysis of prospectively collected data. Objective: To determine which, if any, radiographic parameters are predictive of clinical outcome after cervical disk replacement (CDR) surgery. Summary of Background Data: It is unclear whether radiographic parameters are predictive of outcome after CDR. Methods: An analysis of the radiographic parameters and clinical outcomes of the CDR cohort of the Discover artificial cervical disk IDE trial was performed. Clinical outcome measures included Neck Disability Index (NDI), visual analog pain scale (neck, arm, and shoulder), and SF-36 physical component summary score scores, collected preoperatively and at regularly scheduled postoperative time periods. Patients with at least 1-year follow-up were included. The change in outcomes from baseline was determined at each follow-up interval. The following minimal clinically important difference (MCID) thresholds were applied: −7.5 for NDI, −25 for visual analog pain scale, and +4.1 for physical component summary score. Fifty-six radiographic variables were analyzed to identify factors that may be associated with a poor clinical outcome, defined as failure to achieve the MCID in NDI. Results: A total of 243 patients underwent CDR at 304 levels (182 one level, 61 two level). One hundred seventy-one patients (89 female, 82 male; mean age, 44.2 y; range, 28–67 y) had at least 1-year follow-up. A preoperative disk height of <3.5 mm was associated with a 3.4 times greater risk of not achieving a MCID in NDI ( P =0.018). Increasing the functional spinal unit angle by >3 degrees was associated with a 3.5 times greater risk of not achieving a MCID in NDI ( P =0.016). There were 21/171 patients (25 levels) who did not achieve the NDI MCID threshold. All of these patients had at least1, and 16/21 of these patients had more than 1 abnormal radiographic finding. Seventy percent of treatment levels had severe or bridging heterotopic ossification at 3-years follow-up, the incidence of which increased linearly with time. Conclusions: Several radiographic variables are predictive of clinical outcomes, including decreased preoperative disk space height and excessive postoperative segmental lordosis.